(3GJMGa Phj GdGSJMbGb HHYV eQGO GdeQGOj hRhGFO CHj ESMGbs - (3eMeO Hf CMeO Hf eMeO Hf eMeO Hf Ydj Hf ZGRj GdYKeGfj GdecfGSj , GHf ZGRj , CHh YHO Gddg,J (B919 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdaJGM GdYdje GdNdGbI CeG HYO agPG GJMGa Phi GdESJMbGb s
(3BNQgG (B:s
(3CKfGA HGH GdGHOGd hBNQ eG ajg ef fUQ GdCdajI (B: (3heaYd UMM cGdeaYGd hCda GdGaYGd hGSJaYGd s
(3GdeNWhW YHGQI Yf LeY dTQMjf Ydi CdajI GHf eGdcs
(3aQZ ef JCdjag SfI (B898s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B226s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdabg GdeGdcjs